Analisis Terhadap Perjanjian Kawin Yang Dibuat Setelah Perkawinan Berlangsung Pasca Putusan MK NO.69/PUU-XIII/2015 - Dini novriansyah; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Marriage is a spiritual bond between a man and a woman as husband and wife inorder to form a happy and eternal family (household) based on the One SupremeGodhead. During the marriage there will be a property called mutual property inmarriage which may create a mixture of property between husband and wife, giving riseto a desire to make an agreement between both parties to clarify the ownership rights ofhusband and wife in terms of wealth and others, which is called the prenuptialagreement. The prenuptial agreement is an agreement made by two persons (marriedcouple) prior to marriage. The arrangement of the prenuptial agreement is notregulated in detail but only regulates the timing of its manufacture only and is regulatedin article 29 of law number 1 of 1974 concerning marriage. However, with the decisionof MK no. 69 / PUU-XIII / 2015 cause changes or eviations that cause new problems inthe life of society. Problems to be investigated in this research is about legal certaintyin the decision of the Court. 69 / PUU-XIII / 2015 concerning the prenuptial agreementand how the legal effect of the prenuptial agreement after marriage takes place over theproperty of marriage.Research method / approach used by writer in this research is normative lawresearch. Normative legal research is a literary legal research, because it makes thebook material as the main pedestal in conducting this research. Sources of legalmaterials used are primary sources of legal material, namely the Civil Code (BW), LawNo.1 of 1974 on marriage, and Decree No.69 / PUU-XIII / 2015, for secondary legalmaterials namely the various books, journals, theses, and expert opinions, as well astertiary legal materials namely Indonesian dictionary, legal dictionary, andencyclopedia. The analysis of legal entities in this study was done by processing andanalyzing qualitatively and poured descriptively.The results of the first study to prove that the verdict MK No.69 / PUU-XIII / 2015has not fully provide legal certainty, and on the results of research both prenuptialagreements made after marriage took place separated property between husband andwife without any one party can get part of other party's property.Keywords: Prenuptial Agreement, Legal Certainty, Legal Effect